STUDENT LEARNING AND STUDENT SERVICES: POLICY ISSUES - SchWeber, Claudine (Online Learning, 2008)
An increasing number of students in the United States are involved in online education, according to research by the Sloan Foundation. By fall 2004, approximately 2.6 million students were estimated to be enrolled in at least one online course, an average growth rate of 24.8% from 2003–04; this figure represents a 5% increase over the 2002–03 growth rate. The consequence of this continuing expansion of the e-learning population is that policies with respect to student learning/academic programs will need to be updated or developed; and policies and practices with respect to existing student services, which often provide different support for onsite and distance students or minimize online services, will need to fit the realities of online learning. Given the technological world of the 21st century, it would behoove institutions if such policies applied to all students and services were online. What are the student areas which require policies for online learning to be effective? Issues in four areas seem to dominate: student learning, student services, 24/7 support and outsourcing, and multi-campus/system alignment. Each points to several policy issues, often inter-linked, that need discussion, decisions and implementation practices. The discussion below does not make a distinction between fully online or blended courses, unless noted.